2018
DOI: 10.1002/micr.30287
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic coagulation marker response to musculocutaneous flap ischemia–reperfusion injury and remote ischemic conditioning: An experimental study in a porcine model

Abstract: The local coagulation marker response to musculocutaneous flap ischemia-reperfusion could be measured systemically by moderate hypercoagulation. RIC did not substantially influence coagulation markers following musculocutaneous flap ischemia-reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Finally, RIPC did not influence thrombin generation or secondary hemostasis markers in the present study. In a porcine model, we have shown that remote ischemic conditioning increased ETP but also aPTT during the reperfusion phase of tissue flap ischemia-reperfusion injury [27]. In human studies, remote ischemic conditioning did not influence thrombin generation in healthy men with no ischemic event [26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, RIPC did not influence thrombin generation or secondary hemostasis markers in the present study. In a porcine model, we have shown that remote ischemic conditioning increased ETP but also aPTT during the reperfusion phase of tissue flap ischemia-reperfusion injury [27]. In human studies, remote ischemic conditioning did not influence thrombin generation in healthy men with no ischemic event [26].…”
Section: Discussionmentioning
confidence: 99%
“… 8 The mechanisms of this remote response to injury/reperfusion are related to microvascular dysfunction. 9 , 10 , 11 In our research, slight kidney damage was highly suspected due to increased blood urea nitrogen and serum creatinine concentration. Lastly, we did not use the SJT shoulder straps at the axilla in the swine model.…”
Section: Discussionmentioning
confidence: 61%